Determination of some virulence factors of Citrobacter freundii isolated from Iraqi patients - Mahmood, Asmaa Easa; Atyah, Amidah Ali (Iraqi Journal of Science, 2021)
This study included the isolation and identification of Citrobacter freundii from 220 samples collected from inpatients and outpatients suffering from urinary tract infection (UTI) and identified at the laboratory of the General Samarra Hospital in Samarra City, Iraq. The study was conducted to investigate some of the virulence factors produced by C. freundii. The results showed that 67 isolates were belonging to the C. freundii, with a rate of 30.45%. Twenty eight samples were from inpatients (41.8%) and 39 samples were from outpatients. The bacterial identification was based on cultural and biochemical tests and confirmed by using VITEK2 compact system. Virulence factor results showed that all isolates were not blood hydrolyzing whereas they produced protease. Seven isolates (10.4%) produced biofilm, five from inpatients and two from outpatients, at rates of 17.8% and 5.1%, respectively. The results showed that 17 (25.4%) of the pathogenic isolates were β-lactamase producers, as determined by the iodometric method, twelve of them (17.9%) were from inpatients and 5 (7.5%) from outpatients. Four isolates of C. freundii produced Extended Spectrum Beta-lactamase (ESβL) enzymes, three from inpatients and one from outpatients, with ratios of 4.5% and 1.4%, respectively. Also, the via B gene, which is responsible for virulence factors, was investigated using PCR. The results showed that 12 isolates from inpatients and 4 isolates from outpatients were harboring this gene. The antimicrobial susceptibility testing by Kirby-Bauer’s method showed that all isolates that produced β-lactamase were resistant to antibiotics.